The Freestall Reimagined: Effects on Stall Hygiene and Space Usage in Dairy Cattle - Beaver, Annabelle (Animals (Basel), 2021)
SIMPLE SUMMARY: Lying stalls for dairy cattle are designed to maintain cow hygiene, reduce labor associated with bedding maintenance, and provide cows with a comfortable place to lie down. These considerations can conflict: stall features that, e.g., reduce manure contamination of bedding can make the stall less comfortable, explaining why cows prefer lying in more open spaces. We developed an “alternative” lying area in which traditional freestalls (i.e., in which cattle are not confined to stalls but can move “freely” about the pen) were modified to create larger areas, and flexible stall partitions were included to help maintain cleanliness. We assessed cattle lying behaviour, including lying postures, in this alternative pen compared to both traditional freestalls and an open pack. Not surprisingly, cleanliness was higher in freestalls, but the alternative pen offered substantial improvement in cleanliness over the open pack. There was little difference in postures associated with lying positions (such as lying with limbs outstretched) between the open pack and alternative pen, and both offered greater limb extension compared to freestalls. We conclude that this type of alternative pen can provide producers with the opportunity to improve comfort compared to freestall housing and improve cleanliness compared to housing in an open pack. ABSTRACT: Modern freestall barns for dairy cattle have been constructed with considerations for dairy cow cleanliness; partitions and other stall features such as neck rails are designed to reduce manure contamination of bedding and decrease farm labor. However, cows prefer to lie in more open spaces, including on bedded packs and pasture. We created an “alternative” housing area by modifying a traditional freestall pen and including flexible partitions to create larger lying areas. We assessed cattle lying behaviour, including lying postures, in this alternative pen (ALT) compared to an open pack (OP) and freestalls (FS) with different stocking densities. We also assessed levels of manure contamination across systems. Cleanliness was highest in FS, but ALT provided substantial improvement compared to OP. Cattle spent more time lying down in OP and ALT compared to FS. There were few differences in postures (such as lying with limbs outstretched) between OP and ALT, but cows in both of these systems more often lay in extended positions compared to when they were housed in FS. Housing in OP and ALT was associated with reduced perching for cows with high body weight; perching has been linked to an increased prevalence of both hoof lesions and lameness. Thus, alternative lying areas can offer a solution for producers seeking to provide cattle with the advantages of a more open lying area, while improving hygiene relative to an open pack.